FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PROGRAM PENGENDALIAN KEPENDUDUKAN DI KOTA SEMARANG - Puji Hardati; Sriratna Rahayu’; Iin Karsinah (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2017)
The population is the dimension in development, the population is more and more, while the quality is not enough, to overcome it, various programs have been implemented. This study aims to assess population growth rates; the government's commitment to the success of population and family planning programs; factors influencing Family Planning program. The design of this study using descriptive analytics with a cross-sectional approach. The population is fertile couples, the sample is 243 respondents in 4 subdistricts. Determination of the sample is done by area proportional random sampling. The results showed that population growth in Semarang City was low. The fertility rate of the population of fertile age in population and family planning program is around 79,43%. Factors affecting the family planning program are child ownership, attitudes, spousal support, the extension of extension workers, availability of costs, and media availability, with average results (p> 0.25). The most dominant factor is paired support, with a p-value of 0.000 <α (0.05). The government's commitment is good, but it is still needed to support the population and family planning program in Semarang City.